You can't taste a pickle with your ear - Ziefert, Harriet. frey50; Haley, Amanda (Maplewood, N.J. : Blue Apple Books, 2006)
Explores how each of the five senses is hard at work all day long providing information, warning of danger, and helping us enjoy the world around us.
"A book about your 5 senses"--Cover.
89143
Keywords: Senses and sensation -- Juvenile literature; SENSES AND SENSATION